Answer:
[tex] \frac{2 - 3i}{4 + 2i} = \frac{1 - 8i}{10} [/tex]
Step-by-step explanation:
To simplify an expression like this, we multiply top and ottom of the fraction (denominator and numerator) by the complex conjugate of the bottom (numerator). For a complex expression (a+bi), the complex conjugate is (a−bi). When we do the calculation, it will become clear why this works so well.
Note that (a−bi)/(a−bi) is just the same as 1, so when we do this multiplication the result is the same number we started with.
[tex] \frac{2 - 3i}{4 + 2i} = \frac{2 - 3i}{4 + 2i} \times \frac{4 - 2i}{4 - 2i } \\ = \frac{8 - 12i - 4i + 6 {i}^{2} }{16 + 8i - 8i - 4 {i}^{2} } \\ = \frac{8 - 16i + 6 {i}^{2} }{16 - 4 {i}^{2} } [/tex]
But
[tex] i = \sqrt{ - 1} \: so \: {i}^{2} = - 1 [/tex]
Using this and collecting like terms, we have:
[tex]\frac{8 - 16i + (6 \times - 1) }{16 - 4 ( - 1) } = \frac{2 - 16i}{20} = \frac{1 - 8i}{10} [/tex]